Carbon Fiber Traces in Cracked Surfaces of Mortar Prisms - Heo, G., Kim, J., Yim, C., Venkel, T., Son, J.-Y. (Applied Sciences (Switzerland), 2022)
The traces of carbon fibers along the cracked surfaces of mortar prisms, being 40 mm x 40 mm x 160 mm in size, are studied, assuming that the cracked surfaces in the prisms are the places with the lowest resistance to the stresses they are exposed to. This is to explain why the prisms with 1.0% carbon fibers in volume reveal higher flexural strength than those with 0.5%, 1.5% and 2.0% of fibers. Five distinctive traces of carbon fibers, such as uprootedness, avulsion, separation, overlay and dividedness are observed in the cracked surfaces. As the percentage increases by more than 1.0%, the number of the uprooted fibers reduces, while the numbers of the divided, avulsed and separated fibers increase. The percentage increase induces more fibers to be clustered together and overlap each other to make more divided, avulsed and separated fiber traces. At the same time, the fiber strands are mixed with the mortar to a greater extent. Consequently, the crack surfaces of the prisms with fiber percentages of 1.5% and 2.0% become mostly covered with fiber-laden mortar and cemented fiber clusters. Since the cemented fiber clusters work as air pockets of various volumes and act as the inhomogeneities together with the fiber-laden mortar, the cohesiveness of the mortar is greatly reduced. The deteriorating cohesiveness of the mortar and the increased inhomogeneity cause the reduction in the flexural strength of the prisms in comparison with those with 1.0% carbon fibers.
Keywords: carbon fibers; mortar prisms; flexural strength; cracked surface; four distinctive traces such as uprootedness; avulsion; separation and dividedness